Chimeric Antigen Receptor (CAR) Regulatory T-Cells in Solid Organ Transplantation - Gille, Ilse; Claas, Frans H. J.; Haasnoot, Geert W.; Heemskerk, Mirjam H. M.; Heidt, Sebastiaan (Frontiers in Immunology, 2022)
Solid organ transplantation is the treatment of choice for various end-stage diseases, but requires the continuous need for immunosuppression to prevent allograft rejection. This comes with serious side effects including increased infection rates and development of malignancies. Thus, there is a clinical need to promote transplantation tolerance to prevent organ rejection with minimal or no immunosuppressive treatment. Polyclonal regulatory T-cells (Tregs) are a potential tool to induce transplantation tolerance, but lack specificity and therefore require administration of high doses. Redirecting Tregs towards mismatched donor HLA molecules by modifying these cells with chimeric antigen receptors (CAR) would render Tregs far more effective at preventing allograft rejection. Several studies on HLA-A2 specific CAR Tregs have demonstrated that these cells are highly antigen-specific and show a superior homing capacity to HLA-A2+ allografts compared to polyclonal Tregs. HLA-A2 CAR Tregs have been shown to prolong survival of HLA-A2+ allografts in several pre-clinical humanized mouse models. Although promising, concerns about safety and stability need to be addressed. In this review the current research, obstacles of CAR Treg therapy, and its potential future in solid organ transplantation will be discussed.